A survey on Robotic Vehicles in Autonomous Navigation - Choudhury, Nupur; Mandal, Rupesh (International Journal of Computer Sciences and Engineering, 2015)
This paper deals with the survey based on Robotic navigation the various types of mobility related procedures that are existing for this particular purpose. The paper further explores the vehicles built with robotic technology, its requirement and an existing project that implements the various concepts and principles. The paper presents an overview of the Google Self Driving Car and its principles and further discusses the impact of Radar/LiDAR fusion algorithm in enabling the efficiency of the existing projects that are done in this domain.